(untitled) (Journal of Bangladesh Academy of Sciences, 2020)
This paper considers a variant of the Reve’s puzzle with n (≥1) discs and an evildoer, which can be placed directly on top of a smaller disc any number of times. Denoting by E(n) the minimum number of moves required to solve the new variant, we give a scheme to find the optimality equation satisfied by E(n). We then find an explicit form of E(n). Journal of Bangladesh Academy of Sciences, Vol. 44, No. 1, 53-58, 2020